Distribution and biochemical and genotypic comparison of phosphate solubilizing bacteria in oil palm soils - Nobandegani, Mohammad Bagher Javadi (2008)
Phosphorus (P) is one of the most important elements in crop production. Deficiency of P may occur in crop plant growing in soils, even in the soil containing adequate phosphates. This may be partly due to fact that plants are able to absorb phosphate only in an available form and unfortunately most of the P in soil is not available. Furthermore to increase the production with limited land size, forced the farmers to optimize land use through application of more chemical phosphate fertilizers. Although the phosphate fertilizers applied to the soils is rapidly immobilized after application and become unavailable to the plant. Soil phosphate is rendered available either by plants root or by phosphate solubilizing bacteria (PSB) through secretion of organic acids. Therefore, phosphate solubilizing soil bacteria’ play some part in correcting P deficiency of plants. In this regard, Population distribution of PSB in the soil is one the important factor taken for consideration for application of chemical fertilizers in the field and producing biofertilizers which more environmental friendly .Currently, there is insufficient information on the occurrence of phosphate solubilizing bacteria (PSB) in soil under oil palm cultivation. The objectives of the study was to isolate phosphate solubilizing bacteria (PSB) from the oil palm rhizosphere, determine the distribution and biochemical characterization of PSB, evaluated their ability to solubilize different forms of insoluble phosphate and found the genetic profile comparison of different isolates from different area.. Study was carried out to determine the population distribution of PSB in fertile oil palm soils by Standard Plate Count. The distribution of PSB strains in the rhizosphere of three oil palm field were 3.41 x 108, 3.30 x 107 and 6.73 x 107 c.f.u.mL-1 in UPM, Dengkil and Semenyih respectively. The distribution of PSB in UPM, Dengkil and Semenyih were 3.37 x 107, 1.97 x 107 and 2.58 x 107 c.f.u.mL-1 respectively in the non rhizosphere fractions. Overall the PSB population in the UPM area was higher(3.41 x 108 , 3.37 x 107 )than another location and followed by Semenyih. The percentage of PSB population compared to total bacterial was higher (91.67%) in the rhizosphere of Dengkil. In terms of population distribution, the PSB in Dengkil showed the highest(91.67%) proportion from the total bacteria count of the rhizosphere fraction and 53.69% in the non rhizosphere fraction compared to the other soil locations which have a lower percentage of PSB. The least percentage of PSB was in the non rhizosphere fraction of UPM constituting only 25.34% of the total bacteria population. Distribution of PSB in Semenyih was 40.54% and 34.96% in rhizosphere and non-rhizosphere, compared to total bacteria population, respectively. Generally the percentage of PSB was lower in the non rhizosphere of all three soils compared to the rhizosphere fraction. 16DNR, 23DR and 12DNR were the most effective phosphate solubilizer isolates after eight days of inoculation in National Botanical Institute Phosphate Medium (NBRIP), respectively. The results of culturing the isolates in NBRIP indicated that among all carbon sources, glucose was the best for phosphate solubilization and KNO3 was less effective compared to (NH4)NO3 when it is used as a source of nitrogen. All PSB isolates were acid producers and among isolates, 16DR had the lowest pH after eight days incubation (pH=4.16). The REP–PCR pattern of isolates designated 3DNR, 16DNR, 8DNR, 2UPMR, 31SR, were found to be highly related to one another (>75%) but very distinct from 6UPMR, 8DR, 5DR, 31UPMR. The cluster analysis identified four major groups of A, B, C and D at genetic distance=0.05. Cluster A contained 14 isolates. Cluster B contained eight isolates and cluster C and D is made-up of two isolates 8DR and 6UPMR respectively. Cluster A and B together formed a main cluster at genetic distance of 0.1. Cluster analysis showed great variability of PSB genetic resources in oil palm soils which can be utilized for selection and improvement of the PSB isolates for use in biofertilizers. In conclusion, it could be postulated that the most effective PSB strain (31UPMR) within the population of microorganism in three different oil palm soils was identified by the cluster analysis of REP-PCR pattern and biochemical trait and phosphate solubilizing bacteria from different soil type have different molecular characteristic.